2015
DOI: 10.11648/j.ijnfs.20150402.20
|View full text |Cite
|
Sign up to set email alerts
|

A Milk Product Supplemented with a Herbal Extract for the Prevention of Osteoporosis: Justifications and Clinical Trial

Abstract: When osteoporosis presents as a disease, effective, quick therapeutic remedy is required. Potent effective pharmaceuticals are available. When osteoporosis is only a threat, prevention and not treatment should be a logical better choice. While the past two decades might have followed a radical treatment direction and adverse effects of potent bisphosphonates have started to appear, it is appropriate to explore effective means of using nutritional supplements specific for the maintenance of bone health when onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…What about adding specific bone protective herbs to popular food consumption like milk? An early clinical trial on the addition of one osteoprotective herb Fructus Ligustri Lucidi has given very impressive results and further studies are indicated [14].…”
Section: Resultsmentioning
confidence: 99%
“…What about adding specific bone protective herbs to popular food consumption like milk? An early clinical trial on the addition of one osteoprotective herb Fructus Ligustri Lucidi has given very impressive results and further studies are indicated [14].…”
Section: Resultsmentioning
confidence: 99%